Mataranka bilyi, a new peculiar genus and species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Australia - Hlaváč, Peter (Zootaxa, 2016)
Mataranka bilyi, gen. and sp. nov. is described based on one male collected in the Northern Territory, Australia. The genus is placed into the subtribe Clavigerodina. The summary of all 14 genera of Clavigeritae with 6 antennomeres, Archiclaviger Heller, 1936; Claviger Preysler, 1790; Clavigeropsis Raffray, 1882; Corynotopsis Jeannel, 1951; Dejaegeria Jeannel, 1964; Gericlavodes Jeannel, 1960; Hexamerodes Jeannel, 1959; Mataranka gen. nov.; Mesoleptochir Jeannel, 1959; Palaeoclaviger Reichensperger, 1930; Tapas Besuchet, 2008; Xenalluaudia Raffray, 1913; Xenomussardia Célis, 1975 and Zuluclavodes Hlaváč, 2007, with a short diagnosis is given.